Bird Life - United States. Bureau of Reclamation; Wamstad, C. O. (Oregon Institute of Technology. Library, 1952)
KP-2139-R2 - Klamath Project. Bird Life. Canadian Honker geese and goslings, Tule Lake Sump; May 16, 1952; Bureau of Reclamation Photo by C. O. Wamstad